PRENATAL ATTACHMENT IN A CONTEXT OF EXPERIENCE OF THE FAMILY OF ORIGIN - Radovanović, Mila; Mihić, Ivana (Primenjena psihologija, 2018)
Prenatal attachment is described as a psychological bond that develops during pregnancy from mother to a fetus. Its importance is reflected in the quality of expectant mothers’ care for the fetus, and it is believed that it is the precursor of the development of emotional attachment between a mother and a child, an important aspect of parental identity formation and preparation for responsible and competent parenting. Studies suggest that the patterns that form the parental identity are transmitted through experiences that are internalized and form internal working model whose components make parental representation. Therefore, the aim of this research was to examine the predictive contribution of experience from the family of origin on the development of prenatal attachment. The sample included 91 pregnant women, inpatients from the Department of Obstetrics and Gynecology in Novi Sad, who were hospitalized because of certain health problems during pregnancy. For testing prenatal attachment the Prenatal attachment scale (SPMPV: Hanak, 2009), was used while as a measure of an experience in family of origin a modified Father presence questionnaire (FPQ: Krampe & Newton, 2006) was employed. The results suggests that relationship with one’s own mother has a significant contribution in predicting prenatal attachment. Such resuts are in line with previous research findings that charachteristics of parental behavior are related with experiences with one’s own parents. Those results could reflect the fact that mothers were seen as dominat caregivers in our sample. Also, modeling can play a role in transgenerational transmission of parentning.